Realizing Sustainable Development In Indonesia Through Economic Growth Priorities: Empirical Evidence Vector Error Correction Model (VECM) - Basri, Basri; Aisah, Laras; Abdullah, Abdullah (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Indonesia's journey towards sustainable economic development is closely intertwined with global issues in female labor force participation, environmental policy, and geopolitical dynamics. This study analyzes the causal relationship between economic growth, geopolitical risk, the female labor force, and environmental policy rigor in Indonesia. The data type used is a time series starting in 1992–2022, and it uses the Vector Error Correction Model (VECM) econometric model to identify the causal relationship and reveal the long-run and short-run effects between variables. The results of the analysis show that there is a one-way relationship between geopolitical risk and the female labor force. While the long-run test results show that the female labor force, geopolitical risk, and environmental policy have a significant impact on economic growth, The findings also reveal that there is a short-term effect between environmental policy stringency and economic development. This study emphasizes the importance of holistic and integrative policy formulation by considering the interaction of economic growth, women's participation in the workforce, environmental policy, and geopolitical risk to achieve sustainable development. By examining the causality and interdependence of the complex dynamics occurring in the socio-economic landscape, policymakers are expected to promote inclusive growth, consider environmental aspects, and be sensitive to geopolitical challenges in Indonesia's development trajectory.